Impact of Behavioural Intention on E-Wallet Usage During Covid 19 Period: A Study from Sri Lanka - Sutharsini, J.; Umakanth, N. (Department of Marketing Management, University of Kelaniya, Sri Lanka, 2021)
In recent years, there is a noticeable increase in cashless transactions due to financial technology development. With the enhancement of fin-tech products like e-wallet, most consumers shift from cash based transactions to cashless. In particular, locked down Citizens of the country had no other choice than to stay at home due to the COVID-19 pandemic in Sri Lanka. The social distancing and avoidance of physical touch were the significant measures to escape from the COVID-19 virus. The use of digital transactions and electronic cash transfers was encouraged in every nook and corner of the country. The present empirical study aimed to investigate the significant predictors of behavioral intention on e wallet usage during the COVID-19 period. This study adopted a practical research design to the online survey method to gather e-wallet users' perceptions in the study area by applying an extended technology acceptance model (TAM). The present study follows the quantitative approach to gathering data from 500 respondents using a Google Form. And collected data were analyzed using the regression model. The results indicate that Attitude, perceived usefulness, perceived ease of use, perceived cost, perceived Risk, and COVID – 19 are the positive and significant predictors of e-wallet usage. In contrast, perceived usefulness, Subjective norms, and facilitating conditions do not significantly influence e-wallet usage. Further, e-wallets usage should be encouraged to avoid unnecessary visits to banks, implement social distancing, avoid physical touch while exchanging cash amid the COVID-19 pandemic in Sri Lanka and create a positive attitude among citizens of the country towards the adoption of a cashless economy. Finally, this study helps the digital marketplace's service providers understand the usefulness of using e-wallet for transaction purposes.
Keywords: Behavioral Intention; COVID-19; E-Wallets; Financial Technology; SriLanka; TAM